Surveillance and the experience of the COVID-19 pandemic for formerly incarcerated individuals - Vuolo, Mike (Punishment & society, 2023)
To date, most criminal justice research on COVID-19 has examined the rapid spread within prisons. We shift the focus to reentry via in-depth interviews with formerly incarcerated individuals in central Ohio, specifically focusing on how criminal justice contact affected the pandemic experience. In doing so, we use the experience of the pandemic to build upon criminological theories regarding surveillance, including both classic theories on surveillance during incarceration as well as more recent scholarship on community surveillance, carceral citizenship, and institutional avoidance. Three findings emerged. First, participants felt that the total institution of prison “prepared” them for similar experiences such as pandemic-related isolation. Second, shifts in community supervision formatting, such as those forced by the pandemic, lessened the coercive nature of community supervision, expressed by participants as an increase in autonomy. Third, establishment of institutional connections while incarcerated alleviated institutional avoidance resulting from hyper-surveillance, specifically in the domain of healthcare, which is critical when a public health crisis strikes. While the COVID-19 pandemic affected all, this article highlights how theories of surveillance inform unique aspects of the pandemic for formerly incarcerated individuals, while providing pathways forward for reducing the impact of surveillance.